2021
DOI: 10.3390/ijms22083803
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 Enables EGFR Signaling in Melanoma Cells

Abstract: Receptor tyrosine kinases (RTK) are rarely mutated in cutaneous melanoma, but the expression and activation of several RTK family members are associated with a proinvasive phenotype and therapy resistance. Epidermal growth factor receptor (EGFR) is a member of the RTK family and is only expressed in a subgroup of melanomas with poor prognosis. The insight into regulators of EGFR expression and activation is important for the understanding of the development of this malignant melanoma phenotype. Here, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…We also observed activation in the NRF2 signaling and glutathione redox pathways in PLX/AZD-resistant spheroids (Table ), which may also contribute to temozolomide resistance, as demonstrated in orthotopic glioma xenograft models . NRF2 has also been implicated in regulating EGFR expression in drug-resistant melanoma . In terms of drug efflux, several ABC transporters, ABCC1 and ABCD1, were upregulated in the PLX/AZD-resistant spheroids (Table ) and have also been implicated in a multidrug-resistant phenotype …”
Section: Discussionmentioning
confidence: 99%
“…We also observed activation in the NRF2 signaling and glutathione redox pathways in PLX/AZD-resistant spheroids (Table ), which may also contribute to temozolomide resistance, as demonstrated in orthotopic glioma xenograft models . NRF2 has also been implicated in regulating EGFR expression in drug-resistant melanoma . In terms of drug efflux, several ABC transporters, ABCC1 and ABCD1, were upregulated in the PLX/AZD-resistant spheroids (Table ) and have also been implicated in a multidrug-resistant phenotype …”
Section: Discussionmentioning
confidence: 99%
“…More recently, high Nrf2 expression was found in glioma tissues compared with non-glioma specimens and the natural compound corilagin was shown to downregulate Nrf2 expression and to induce apoptosis in glioma models [ 72 ]. Nrf2 was also upregulated in melanoma enhancing tumour malignancy by blocking differentiation and inducing COX2 expression [ 73 ] and promoting EGFR mediated oncogenic signalling [ 74 ]. Alternative splicing mechanisms in the Nrf2 transcript may also contribute to loss of the Keap1 binding domain and Nrf2 hyperactivation.…”
Section: The Dual Role Of Nrf2 In Cancermentioning
confidence: 99%
“…A recent study demonstrated that stress-induced NRF2 binds to the ARE in the EGF promoter and leads to elevation of soluble EGF, while simultaneously blocking MITF activity, resulting in derepression of EGFR and TGFA [ 19 ]. This leads to EGFR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of EGFR in melanoma establishes a pro-metastatic phenotype [ 17 ] that can activate Ras/MAPK, PLCγ1/PKC, Akt, and STAT, which subsequently stimulate cell proliferation, migration, invasion, survival, and differentiation. The receptor tyrosine kinase EGFR is activated in a subset of melanoma cells [ 18 , 19 ] where its expression correlates with poor prognosis in human melanoma [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%